Recent advances in the study of mercury biogeochemistry in Arctic permafrost ecosystems - Malcata Martins, Beatriz (2025)
Permafrost predominates in polar and high mountain regions, encompassing nearly 15 % of the exposed land in the Northern Hemisphere. It denotes soil or rock that remains at or below 0 °C for the duration of at least two consecutive years. These frozen soils serve as a barrier to contaminants that are stored and accumulated in permafrost over extended periods of time. One of these chemical compounds is mercury (Hg), a heavy metal well recognized for its severe toxic effects. Mercury presents a major risk worldwide to ecosystems, biota and human health and is strengthened by the Minamata Convention on Mercury. The International Panel on Climate Change (IPCC) scientific group monitors and assesses the science related to climate change and highlights the significant impacts of global warming. The phenomenon known as Arctic amplification has accentuated warming of the Arctic in recent years and has led to the degradation and rapid thawing of permafrost. This process has significant implications in hydrology of the ecosystems and for the mobility of previously sequestered carbon and trace metals, such as Hg, with possible adverse environmental and human health impacts. In this article, we provide a comprehensive review of the current understanding of the Hg cycle in permafrost regions, exploring the effects of global warming on these intricate processes. Additionally, we highlight existing research gaps and propose directions for future investigations.